2019
DOI: 10.1590/2317-6431-2018-2063
|View full text |Cite
|
Sign up to set email alerts
|

As dificuldades no atendimento aos indivíduos com doenças neurodegenerativas: o fonoaudiólogo e a equipe multiprofissional

Abstract: RESUMO Objetivo Analisar as dificuldades de fonoaudiólogos quanto à intervenção fonoaudiológica em indivíduos com doenças neurodegenerativas. Métodos Trata-se de um estudo transversal com 74 fonoaudiólogos brasileiros. Os profissionais foram convidados, por meio de redes sociais, a responder um questionário online com perguntas sobre sua atuação profissional com indivíduos com doenças neurodegenerativas. Foram incluídos apenas fonoaudiólogos que atuavam no território brasileiro e que atendiam, ou já haviam a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
0
4
0
4
Order By: Relevance
“…As for the mapping of the place where they practiced their profession, historically the largest number of speech therapists has been concentrated in the Southeast Region of Brazil (13) . The present study also demonstrated the predominance of professionals in this region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the mapping of the place where they practiced their profession, historically the largest number of speech therapists has been concentrated in the Southeast Region of Brazil (13) . The present study also demonstrated the predominance of professionals in this region.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of working in private practice, as discussed in another study (15) , considers the training of speech therapists to be predominantly rehabilitative, in which clinical scenarios have been privileged (15) . Another study (13) considered that the mixed performance evidences panoramas and difficulties that can be encountered regardless of the type of care network (private or public), which leads the speech therapist to establish both employment relationships, without neglecting either of the two sectors (13) .…”
Section: Discussionmentioning
confidence: 99%
“…Quanto ao mapeamento do local em que exerciam a profissão, historicamente o maior número de fonoaudiólogos tem se concentrado na Região Sudeste do Brasil (13) . O presente estudo também demonstrou a predominância de profissionais nessa região.…”
Section: Discussionunclassified
“…A prevalência de atuação no consultório particular, tal como discutido em outro estudo (15) , considera a formação do fonoaudiólogo predominantemente reabilitadora, na qual têm sido privilegiados cenários clínicos (15) . Outro estudo (13) considerou que a atuação mista evidencia panoramas e dificuldades que podem ser encontrados independentemente do tipo de rede de assistência (privada ou pública), o que leva o fonoaudiólogo a estabelecer ambos os vínculos empregatícios, sem preterir nenhum dos dois setores (13) .…”
Section: Discussionunclassified
“…Clarifying these questions allows for the development of an appropriate intervention plan and the definition of the most suitable courses of action. Unfortunately, speech and language symptoms may manifest even before assessment scores fall outside the normal ranges [43]. Furthermore, their presence can be very subtle and may not be perceived by the patient, such as in the case of dysphagia or cognitive and language impairments.…”
Section: Introductionmentioning
confidence: 99%